New patient-reported outcome measure to assess perceived barriers to antiretroviral therapy adherence: the PEDIA scale - Celline Cardoso Almeida-Brasil; Elizabeth do Nascimento; Micheline Rosa Silveira; Palmira de Fátima Bonolo; Maria das Graças Braga Ceccato
Abstract: This study sought to develop and evaluate a new patient-reported outcome measure to assess perceived barriers to antiretroviral therapy (ART) adherence. The Perceived Barriers to Antiretroviral Therapy Adherence (PEDIA) scale was developed based on individual interviews with patients. After pilot testing and assessing the evidence based on content analysis, the scale's revisions resulted in a 40-item version. The PEDIA was applied to 415 HIV-infected adults receiving ART for a maximum of 180 days, recruited from three healthcare facilities of reference in the city of Belo Horizonte, Minas Gerais State, Brazil. The analyses included exploratory factor analysis, internal consistency, item response theory, temporal stability, and predictive test-criterion relationship. The scale's final version contains 18 items distributed in three dimensions, as follows: cognitive and routine problems (4 items); medication and health concerns (6 items); and patient's fears and feelings (8 items). The results of McDonald's omega and temporal stability demonstrate that the PEDIA is internally consistent and yields stable scores over time. The assessment of the information's functions suggested that the three dimensions were informative for assessing a broad range of latent traits. Evidence concerning the test-criterion relationship confirmed that the PEDIA was able to predict non-adherence three months later. Our findings suggest that the PEDIA is a psychometrically adequate tool for evaluating perceived barriers in adult patients initiating ART. It could be used in both research and clinical practice for the early detection of patients at risk of non-adherence and for the identification of potentially modifiable barriers.